Perbedaan Metode Brainstorming Dengan Metode Eskpositori Terhadap Kemampuan Komunikasi Matematis Siswa - Ach. Nafi'udin; Ani Afifah; Miftahul Khoiri (Arfah BHMS Foundation, 2026)
This study aims to determine the differences in mathematical communication skills of students taught using the brainstorming learning method and those taught using the expository learning method. This quantitative study used a quasi-experimental research method and a randomized pretest-posttest control group design. The population was grade VII of Darul Ulum Ngemplakrejo Junior High School, Pasuruan City. The sample consisted of grades VII-A as the experimental class and VII-B as the control class. The sampling technique used in this study was total sampling. Data analysis techniques used were normality test, homogeneity test, and gain test. Based on the results and data analysis, it can be concluded that there is a significant difference in the N-Gain Score for the experimental class using the brainstorming learning method, categorized as high with an average score of 78.9%, and the control class using the expository learning method, categorized as medium with an average score of 36.8%.